2018
DOI: 10.1039/c7fo01887h
|View full text |Cite
|
Sign up to set email alerts
|

Fermentation of non-digestible raffinose family oligosaccharides and galactomannans by probiotics

Abstract: Due to their prebiotic potential indigestible oligosaccharides became a major focus of research interest. In this study the growth of selected probiotic strains including lactobacilli, bifidobacteria, Lactococcus lactis, Streptococcus salivarius ssp. thermophilus, Pediococcus ssp. and Enterococcus faecium with the, raffinose family oligosaccharides (RFOs) raffinose, stachyose and verbascose and galactomannan from guar bean Cyamopsis tetragonoloba (total guar carbohydrates, oligosaccharides (dp 2-4) and polysac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(44 citation statements)
references
References 22 publications
0
43
0
1
Order By: Relevance
“…However, in this work the unclassified specie of Streptococcus was not particularly plentiful. Similarly, Lactobacillus is a widely reported genus that comprises of several probiotic species that can metabolize raffinose carbohydrate and oligosaccharides [52]. Weissella genus is reported as possessing phosphotransferase systems of β-glucosidase and α-galactosidase genes for metabolizing D-cellobiose and D-raffinose [53], but their metabolic capacity was unobserved.…”
Section: Changes Of Microbial Composition During Mango (Mangifera Indmentioning
confidence: 99%
“…However, in this work the unclassified specie of Streptococcus was not particularly plentiful. Similarly, Lactobacillus is a widely reported genus that comprises of several probiotic species that can metabolize raffinose carbohydrate and oligosaccharides [52]. Weissella genus is reported as possessing phosphotransferase systems of β-glucosidase and α-galactosidase genes for metabolizing D-cellobiose and D-raffinose [53], but their metabolic capacity was unobserved.…”
Section: Changes Of Microbial Composition During Mango (Mangifera Indmentioning
confidence: 99%
“…[17] Several studies have reported that STA stimulates the growth of Lactobacillus and Bifidobacterium in the intestinal tract, inhibits enteric bacilli, and prevents intestinal damage. [18][19][20] The STA-enriched -Galactooligosaccharides stachyose could modulate the profile of intestinal microbiota and enhance the intestinal mucosal barrier function of fish. [21] Soybean oligosaccharides including STA promote cellular immunity, humoral immunity, nonspecific immunity, and immunoglobulin levels in mice.…”
Section: Introductionmentioning
confidence: 99%
“…Untuk menghidrolisis komponen tersebut, diperlukan enzim α-galaktosidase yang dihasilkan oleh BAL 27 . Namun, jenis BAL yang digunakan dalam penelitian ini diketahui memiliki tingkat reaktivitas enzim αgalaktosidase rendah 28 . Tingkat viskositas soyghurt yang semakin tinggi akan menghambat pertumbuhan BAL.…”
Section: Hasil Total Balunclassified